Parental Attitude as a Determinant of Psychological Disorders among Young Adults - Maryam Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Psychological disturbance among young adults is a critical challenge nowadays and the reasons for this group being suffered from such issues are complex. Aim: To explore the determinant of psychological issues among Pakistani youngsters. Focusing on the causes of mental turbulences related to anxiousness, oppositional defiance disorder, intermittent explosive disorder, borderline personality, bipolar disorder, and psychosocial stressors, the attempt investigated: understanding of the problem and risk factors, social support and contextual factors, factors being perceived as alleviating low mood, despair, rage, pain, hopelessness, et cetera. Method: Three case studies of two boys and one girl aged 20-25 having been diagnosed with the above-mentioned disruptive and depressive disorders are presented incorporating a qualitative approach. It includes semi-structured interviews, a survey, and phenomenological considerations. Finding: The thematic analysis and thorough review of case studies present the indifferent attitude of parents and their harshness are the dominant and consistent determinants of ill-functioning among the involved participants. All complaints of participants were directly or indirectly associated with familial practices, particularly with parental attitude. Practical Implications. The significant role of parents in the childs’ development can never be denied. Therefore, the study provides an insight for the proper exploration of the parent-child relation and attempts to reduce or vanish the discrepencies, must be the goal of therapy. Also, awarness or the specified sessions as a reminder for good parenting regarding thepotential influence of parental attitude and involvement might be the effective attempt for the healthy functioning of the child. Conclusion.Consequently, a comprehensive model with parental involvement and realization of their influences on an individual’s mental health should be formulated and emphasized for the prevention of further cases and management of current ones. Keywords: Case studies, determinants, disorders, mental health, parental attitude.